King returns to Washington : explorations of memory, rhetoric, and politics in the Martin Luther King, Jr. National Memorial /: explorations of memory, rhetoric, and politics in the Martin Luther King, Jr. National Memorial. (2015) - Walker, Jefferson
No abstract available